Agricultural Sector Efforts in Dealing with Climate Change in Huntu Barat Village, South Bulango District, Bone Bolango Regency - Sulis Nur Hidayah; Aziz Akbar Mukasyaf (Dinasti International Journal of Education Management And Social Science, 2025)
Global climate change, marked by rising temperatures and extreme weather phenomena, has significantly impacted Huntu Barat Village's agricultural sector, Bulango Selatan Subdistrict, Bone Bolango Regency. Most of residents of West Huntu rely on agriculture as their main source of livelihood, playing a crucial role in the local economy. Therefore, it is important to understand how farmers in this village are adapting to climate change. This study aims to (1) comprehensively identify the adaptation practices implemented by farmers in Huntu Barat Village, and (2) analyze the impacts of these practices in addressing climate change. The research employs a qualitative descriptive approach through observation and in-depth interviews with farmers, agricultural extension officers, and village officials. The study's findings indicate that the adaptation strategies applied include the selection of crop varieties that are resilient to extreme conditions, the use of organic inputs such as fermented cow urine and rice straw mulch to maintain soil fertility, and the utilization of river irrigation accompanied by simple technologies to ensure even water distribution. The integration of traditional farming techniques with local innovations not only enhances productivity and food security but also supports environmental sustainability. The synergy among these various practices demonstrates that locally implemented adaptation solutions can effectively mitigate the negative impacts of climate change and serve as a relevant model for developing agricultural strategies in other regions.